H-Reflex and delayed-onset muscle soreness in the trapezius muscle - Vangsgaard, S.; Sogaard, K.; Taylor, J. L.; Madeleine, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The separation of the efferent and afferent fibres to trapezius enables H reflexes to be evoked by electrical stimulation without the influence of direct activation of the motor axons (1). Delayed-onset muscle soreness (DOMS) often occurs in relation to sports activities as a result of high-intensity eccentric exercise (2). No studies have investigated the effects of DOMS on the H reflex in the trapezius muscle. The objective of this study was to investigate the modulation of the H reflex 24 h after eccentric exercise in the presence of DOMS. Methods H reflexes were recorded from the dominant middle trapezius muscle by electrical stimulation of the C3/4 cervical nerve in 10 healthy subjects. DOMS was induced by eccentric exercise of the dominant shoulder. H reflexes were obtained in tree sessions: "24h before", "Pre", and "24h after" eccentric exercise. Ratios of maximal H reflex and M wave responses (Hmax/Mmax) were compared between sessions. Additionally, a between session comparison was done for the ratios of H reflex amplitudes (Hi_75/Mmax, and Hi_50/Mmax) obtained from the stimulus intensity needed to obtain 75% and 50% of Hmax at "24h before ". Muscle soreness was assessed using a visual analogue scale (VAS) score and measures of pressure pain threshold (PPT). Results A decrease in both Hi_75/Mmax and Hi_50/Mmax were observed at "24h after", (P<0.05). VAS scores were significantly higher at "24h after" compared with "24h before" and "pre", (P<0.05). PPT values were significantly lower "24h after" compared to "24h before" and "pre", (P<0.05). Discussion This study presented evidence that at 24h after exercise stronger stimulus intensity was needed to reach the same magnitude of the H reflex as the recruitment curve was shifted to the right. This modulation of the stimulus- response relationship could be caused by presynaptic inhibition of Ia afferent fibres` input to the motoneuron by group III and IV afferents